Method for improving light transmittance of n-hexane
Through oxidation treatment, adsorption removal and distillation removal methods, the problem of low light transmittance of n-hexane is solved, significantly improves detection sensitivity and background noise, and realizes high-purity and high light transmittance preparation of n-hexane. for liquid chromatography.
Patent Information
- Application Number
- CN202411394472.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, the light transmittance of n-hexane leads to a decrease in the intensity of the liquid chromatography detection signal and an increase in background noise, affecting the identification and quantitative analysis of detection sensitivity and peaks.
The third-level purification process of oxidation treatment, adsorption removal and distillation removal is adopted, and aromatic hydrocarbons and double bond impurities are removed by ozone oxidation treatment, and the adsorption removal is carried out by modified molecular sieve, and a high light transmittance is obtained through distillation. alkyl.
It significantly improves the light transmittance of n-hexane, improves detection sensitivity, reduces background noise, and ensures high purity and high light transmittance n-hexane products, suitable for liquid chromatography applications.
Smart Images

Figure CN119241328A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of n-hexane purification, and in particular to a method for improving the light transmittance of n-hexane. Background Art
[0002] Hexane is an organic compound with the molecular formula C6H 14 It belongs to the class of straight-chain saturated aliphatic hydrocarbon compounds and is a colorless liquid with a faint special odor. n-Hexane is volatile, almost insoluble in water, and easily soluble in chloroform, ether, and ethanol. In the prior art, n-hexane is mainly used as a solvent, such as a vegetable oil extraction solvent, a propylene polymerization solvent, a rubber and coating solvent, a pigment diluent, etc., and is used for the extraction of various edible oils and fats such as soybeans, rice bran, and cottonseeds, and oils and fats in spices. In addition, n-hexane isomerization is one of the important processes for producing high-octane gasoline blending components.
[0003] n-Hexane can be used as a non-polar mobile phase in high performance liquid chromatography (HPLC), mainly used to separate non-polar and medium polar compounds. At the same time, in liquid chromatography, the polarity of the mobile phase can be adjusted by combining n-hexane with other polar solvents (such as ethanol, methanol, acetonitrile, etc.), thereby improving the separation effect. Since some specific impurities in n-hexane will have specific absorption peaks in the ultraviolet region, which may affect the liquid chromatography test results, in the application of liquid chromatography, the transmittance of n-hexane in the range of 225-400nm is usually required to be higher, generally higher than 90% before it can be used as a non-polar mobile phase for liquid chromatography.
[0004] However, in the prior art, n-hexane is generally prepared by cracking and fractionating crude oil. Aromatic hydrocarbons such as benzene, toluene, xylene and other impurities may be generated during the cracking process. At the same time, double-bond compounds such as alcohols, ethers, ketones and other impurities may also be generated during the synthesis of n-hexane. These impurities will directly lead to a decrease in the transmittance of n-hexane. The low transmittance of n-hexane may cause a decrease in the signal intensity received by the liquid chromatography detector, thereby affecting the sensitivity of the detection. At the same time, the low transmittance of n-hexane may also cause additional background noise, resulting in unstable baselines, affecting peak identification and quantitative analysis.
[0005] Therefore, in view of the above-mentioned technical defects, providing a method that can effectively improve the light transmittance of n-hexane has important technical significance. Summary of the invention
[0006] In order to solve the technical problems existing in the prior art, the present invention provides a method for improving the light transmittance of n-hexane, which can effectively treat impurities (such as aromatic hydrocarbon impurities, oxygen-containing compound impurities, etc.) generated in the process of preparing n-hexane, and can effectively improve the light transmittance of n-hexane, thereby avoiding the problems that low-transmittance n-hexane affects the detection sensitivity, reduces the signal intensity, causes background noise, etc. in liquid chromatography applications.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for improving the light transmittance of n-hexane comprises the following steps: oxidation treatment, adsorption removal, and distillation to remove impurities.
[0008] The oxidation treatment method is as follows: adding industrial-grade n-hexane into an oxidation reactor, then connecting a reaction bottle and an ozone generator to ensure that the device system is well sealed; then placing the oxidation reactor in an ice-water bath, controlling the temperature of the oxidation reactor within a range of 0-5°C to avoid overheating and unnecessary side reactions; then turning on the ozone generator, controlling the ozone flow rate to 0.1-1L / min, and the ozone pressure to 0.2-0.5MPa, introducing ozone into the oxidation reactor, and controlling the temperature and stirring the reaction for 2-3h to complete the oxidation treatment; then, under stirring conditions, introducing an inert gas into the oxidation reactor to completely replace the ozone in the oxidation reactor to obtain an oxidizing liquid.
[0009] In the oxidation treatment, the industrial-grade n-hexane is prepared by cracking and fractionating crude oil; conventional commercially available industrial-grade n-hexane prepared by the crude oil cracking method can be used.
[0010] Preferably, the ozone flow rate is controlled to be 0.4-0.8 L / min.
[0011] The adsorption removal method is to completely fill the adsorption column with the modified molecular sieve, and pay attention to avoid filling dead corners and pores during the filling process; after the filling is completed, the adsorption column is connected to the flow meter and the collector to ensure that the device system is well sealed; the flow meter is turned on, the flushing flow of the oxidizing liquid is controlled to be 10-15mL / min, and the modified molecular sieve in the adsorption column is flushed with the oxidizing liquid for 3-5 times; after the flushing is completed, the flow rate of the oxidizing liquid is adjusted to 4-5mL / min, and the oxidizing liquid continues to flow through the adsorption column for continuous adsorption and removal to obtain an adsorption removal liquid.
[0012] In the adsorption removal, the amount of oxidation liquid used for each flushing is 550-600 mL.
[0013] The modified molecular sieve is prepared by the following steps: pretreatment, composite modification and post-treatment.
[0014] The pretreatment method comprises placing the 3A molecular sieve in a calcining furnace, heating it to 400-500°C in an inert gas environment, keeping it warm for 40-60 minutes to remove impurities, and naturally cooling it to room temperature to obtain a heat-treated product; then putting the heat-treated product into an ethanol solution with a volume concentration of 88-92%, stirring it for 20-30 minutes, stirring and heating it to 40-45°C, keeping it warm and stirring, and simultaneously dropping a silane coupling agent KH-792 and a di(dioctyl pyrophosphate) acyloxy The method comprises the following steps: adding silane coupling agent KH-792 and bis(dioctyl pyrophosphate acyloxy)ethylene titanate, and controlling the dropping time of silane coupling agent KH-792 and bis(dioctyl pyrophosphate acyloxy)ethylene titanate to be 50-60min; after the dropping is completed, the stirring is continued for 7-8h, and the solid is separated by centrifugation at 11000-12000rpm. The solid is washed with deionized water, and then placed in a vacuum drying oven, and dried at 80-85℃ for 12-14h in a vacuum degree of 0.07-0.08MPa to obtain a pretreated product.
[0015] In the pretreatment, the weight ratio of 3A molecular sieve, ethanol solution, silane coupling agent KH-792, and bis(dioctyl pyrophosphate acyloxy)ethylene titanate is 9-10:60-65:1-1.2:0.3-0.4.
[0016] The composite modification method comprises the following steps: adding the pretreated material into 8-9 times the weight of deionized water, stirring for 10-20 minutes, then adding tetrapropylammonium hydroxide, stirring for 20-30 minutes; then adding isopropyl aluminum and ethyl orthosilicate, stirring and heating to 30-35° C., keeping the temperature and stirring for 60-90 minutes, then continuing to stir and heating to 85-90° C., keeping the temperature and stirring for 22-24 hours, to obtain a precursor solution; then transferring the precursor solution into a high-pressure reactor, heating to 170° C., and stirring for 15 minutes. -180℃, keep warm for crystallization for 55-60h, separate the solid by centrifugation at 9500-10000rpm, wash the solid with anhydrous ethanol and deionized water in turn, place it in a vacuum drying oven, dry it at 100-105℃ for 12-14h in a vacuum environment of 0.08-0.09MPa; then transfer it to a calcining furnace, heat it to 550-600℃ at a heating rate of 3-4℃ / min, keep warm for 4-5h, and naturally cool it to room temperature to obtain a calcined product.
[0017] In the composite modification, the weight ratio of the pretreated material, tetrapropylammonium hydroxide, isopropyl aluminum and tetraethyl orthosilicate is 10-10.5:2-2.3:0.12-0.15:3.9-4.1.
[0018] The post-treatment method comprises the following steps: immersing the calcined product in an ammonium nitrate solution of 4-5 times its weight, stirring and heating to 75-80°C, heat-insulating for 8-9 hours, centrifuging at 9500-10000rpm to separate solids, washing the solids with deionized water, placing the solids in a vacuum drying oven, drying at 100-105°C for 12-14 hours in an environment of vacuum degree of 0.08-0.09MPa; then transferring the solids into a calcining furnace, heating to 400-420°C at a heating rate of 1.2-1.6°C / min, heat-insulating and calcining for 2-3 hours, and naturally cooling the solids to room temperature to obtain the modified molecular sieve.
[0019] In the post-treatment, the molar concentration of the ammonium nitrate solution is 0.2-0.22 mol / L.
[0020] The distillation impurity removal method comprises the following steps: introducing the adsorbed removal liquid into a distillation kettle, starting the stirring heating and light component condensation system of the distillation kettle, setting the heating temperature of the distillation kettle to 130-150°C, and setting the light component condensation temperature to 8-10°C; controlling the temperature of the distillation kettle to rise to 130-150°C under stirring conditions, and performing heat preservation distillation; performing total reflux for the first 1-2 hours of heat preservation distillation to promote the liquid phase and the gas phase in the distillation kettle to reach equilibrium, thereby facilitating the subsequent separation process; after the total reflux is completed, adjusting the reflux ratio to 4:1-6, controlling the liquid phase temperature to 65-75°C, and the gas phase temperature to 55-65°C, extracting the n-hexane fraction, and obtaining high-transmittance n-hexane.
[0021] Preferably, after the total reflux is completed, the reflux ratio is adjusted to 4:3-6.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for improving the light transmittance of n-hexane of the present invention adopts a three-stage purification process of oxidation-adsorption-distillation. In the oxidation treatment step, ozone is used as an oxidant to oxidize the industrial-grade n-hexane raw material, effectively removing aromatic hydrocarbon impurities (such as benzene, toluene, xylene, etc.) and double bond impurities (such as alcohol, ether, ketone, etc.) that affect ultraviolet absorption. The reaction conditions are mild and easy to control. The oxidation treatment effect is good and no new impurities are introduced to obtain an oxidized liquid. Then, the oxidized liquid continuously flows through an adsorption column filled with a modified molecular sieve for adsorption removal. The impurities in the n-hexane ( In particular, the isomeric impurities of n-hexane are selectively adsorbed, which effectively overcomes the problem that the isomeric impurities in n-hexane are close to the boiling point and difficult to separate; at the same time, in the preparation of the modified molecular sieve, the 3A molecular sieve is pre-modified by using a bisaminosilane coupling agent and a chelating titanate coupling agent to promote the combination performance of the 3A molecular sieve and the in-situ generated ZSM molecular sieve in the subsequent composite modification step, and improve the long-term adsorption stability and adsorption effect of the modified molecular sieve finally prepared in continuous adsorption and removal; in the composite modification step, The pretreated product is used in the preparation process of ZSM molecular sieves, and the 3A molecular sieve is further compounded with the original ZSM molecular sieve by in-situ compounding, so as to achieve the coordination of large and small pores of the modified molecular sieve, improve its selective adsorption performance of impurities in the oxidizing solution, and synergistically improve the long-term adsorption stability and adsorption effect of the modified molecular sieve in continuous adsorption and removal; then in the post-treatment step, ammonium nitrate is used to perform ion exchange on the roasted product, and the pore structure of the modified molecular sieve is further optimized, so as to further improve the selectivity of the modified molecular sieve for impurities in continuous adsorption and removal. Adsorption performance and long-term adsorption stability; finally, the adsorption removal liquid is distilled and impurity-removed to obtain high-transmittance n-hexane; the aforementioned technical means cooperate and work synergistically with each other to effectively simplify the treatment process, and through the three steps of oxidation-adsorption-distillation, it can effectively treat the impurities (such as aromatic hydrocarbon impurities, oxygen-containing compound impurities, etc.) generated in the preparation process of n-hexane, and the adsorption effect on impurities in n-hexane is significant, effectively improving the transmittance of n-hexane, thereby avoiding the problems of low-transmittance n-hexane affecting detection sensitivity, reducing signal intensity, and causing background noise in liquid chromatography applications.
[0023] (2) The method for improving the light transmittance of n-hexane of the present invention has a purity of ≥99.6% and a water content of not more than 0.004% and an acidity (measured in H +The transmittance of n-hexane at 195nm is greater than 21.5%; at 210nm, the transmittance of n-hexane is greater than 72.5%; at 220-260nm, the transmittance of n-hexane is greater than 89.5%; at 260-400nm, the transmittance of n-hexane is close to 100%.
[0024] (3) The method for improving the light transmittance of n-hexane of the present invention uses a modified molecular sieve for continuous adsorption and removal for 240 hours, and the purity of the obtained high-transmittance n-hexane is 99.6%, the water content is 0.005%, and the acidity (in terms of H + The transmittance of n-hexane at 195nm was 21.8%; at 210nm, the transmittance of n-hexane was 71.6%; at 220nm, the transmittance of n-hexane was 88.2%; at 225nm, the transmittance of n-hexane was 91.7%; at 260nm, the transmittance of n-hexane was 99.8%; at 280nm, the transmittance of n-hexane was 99.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a line graph of the transmittance of n-hexane at various wavelengths in Example 1.
[0026] In the figure, the transmittance of the n-hexane raw material (ie, industrial-grade n-hexane) in Example 1, the n-hexane after oxidation treatment, the n-hexane after adsorption removal, and the n-hexane after distillation and impurity removal at various wavelengths are shown respectively. DETAILED DESCRIPTION
[0027] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0028] Example 1 This embodiment provides a method for improving the light transmittance of n-hexane, specifically: 1. Oxidation treatment Add industrial-grade n-hexane into the oxidation reactor, and then connect the reaction bottle and the ozone generator to ensure that the device system is well sealed; then place the oxidation reactor in an ice-water bath, and control the temperature of the oxidation reactor within the range of 0-5°C to avoid overheating and unnecessary side reactions; then turn on the ozone generator, control the ozone flow rate to 0.6L / min, and the ozone pressure to 0.3MPa, introduce ozone into the oxidation reactor, control the temperature and stir the reaction for 2.5h, and then complete the oxidation treatment; then, under stirring conditions, introduce inert gas (nitrogen) into the oxidation reactor to completely replace the ozone in the oxidation reactor to obtain an oxidized liquid (i.e., n-hexane after oxidation treatment).
[0029] Among them, industrial-grade n-hexane is prepared by cracking and fractionating crude oil; this embodiment uses conventional commercially available industrial-grade n-hexane prepared by the crude oil cracking method.
[0030] 2. Adsorption removal The modified molecular sieve is used to completely fill the adsorption column, and attention is paid to avoid filling dead corners and pores during the filling process; after the filling is completed, the adsorption column is connected to the flow meter and the collector to ensure that the device system is well sealed; the flow meter is turned on, the flushing flow rate of the oxidizing liquid is controlled to be 12mL / min, and the modified molecular sieve in the adsorption column is flushed with the oxidizing liquid for 4 times; after the flushing is completed, the flow rate of the oxidizing liquid is adjusted to 4.5mL / min, and the oxidizing liquid continues to flow through the adsorption column for continuous adsorption and removal to obtain the adsorption and removal liquid.
[0031] The amount of oxidation liquid used for each flushing is 570 mL.
[0032] The preparation method of the modified molecular sieve is as follows: 1) Preprocessing The 3A molecular sieve was placed in a calcining furnace, heated to 450°C in an inert gas (nitrogen) environment, kept warm for 50 minutes to remove impurities, and naturally cooled to room temperature to obtain a heat-treated product; the heat-treated product was then put into an ethanol solution with a volume concentration of 90%, stirred for 25 minutes, stirred and heated to 42°C, and the silane coupling agent KH-792 and bis(dioctyl pyrophosphate)ethylene titanate were dripped into the solution while being kept warm and stirred, and the dripping time of the silane coupling agent KH-792 and bis(dioctyl pyrophosphate)ethylene titanate was controlled to be 55 minutes; after the dripping was completed, the solution was kept warm and stirred for 7.5 hours, and the solid was separated by centrifugation at 11500rpm. The solid was washed with deionized water, placed in a vacuum drying oven, and dried at 82°C for 13 hours in a vacuum environment of 0.075MPa to obtain a pretreated product.
[0033] Among them, the weight ratio of 3A molecular sieve, ethanol solution, silane coupling agent KH-792, and bis(dioctyl pyrophosphate)ethylene titanate is 9.5:63:1.1:0.35.
[0034] 2) Composite modification The pretreated material was put into 8.5 times the weight of deionized water, stirred for 15 minutes, and then tetrapropylammonium hydroxide was added and stirred for 25 minutes; isopropyl aluminum and ethyl orthosilicate were added, stirred and heated to 32°C, kept stirring for 70 minutes, and then continued to stir and heat to 88°C, kept stirring for 23 hours to obtain a precursor solution; then the precursor solution was transferred to a high-pressure reactor, heated to 175°C, kept warm for crystallization for 58 hours, and then the solid was separated by centrifugation at 9800rpm. After the solid was washed with anhydrous ethanol and deionized water in turn, it was placed in a vacuum drying oven and dried at 102°C for 13 hours in a vacuum environment of 0.085MPa; then it was transferred to a calcining furnace, heated to 580°C at a heating rate of 3.5°C / min, kept warm for 4.5 hours, and naturally cooled to room temperature to obtain a calcined material.
[0035] The weight ratio of the pretreated material, tetrapropylammonium hydroxide, isopropyl aluminum and tetraethyl orthosilicate is 10.3:2.2:0.13:4.
[0036] 3) Post-processing The calcined product was immersed in 4.5 times the weight of ammonium nitrate solution, stirred and heated to 88°C, kept warm for 8.5 hours, and then centrifuged at 9800rpm to separate the solid. After the solid was washed with deionized water, it was placed in a vacuum drying oven and dried at 102°C for 13 hours in a vacuum environment of 0.085MPa; then it was transferred to a calcining furnace, heated to 410°C at a heating rate of 1.5°C / min, kept warm and calcined for 2.5 hours, and naturally cooled to room temperature to obtain a modified molecular sieve.
[0037] Wherein, the molar concentration of the ammonium nitrate solution is 0.21 mol / L.
[0038] 3. Distillation and impurity removal The adsorbed removal liquid is introduced into the distillation kettle, and the stirring heating and light component condensation systems of the distillation kettle are turned on. The heating temperature of the distillation kettle is set to 140°C, and the light component condensation temperature is set to 9°C. Under stirring conditions, the temperature of the distillation kettle is controlled to rise to 140°C, and the distillation is kept warm. During the first 1.5 hours of the distillation, full reflux is performed to promote the equilibrium between the liquid and gas phases in the distillation kettle, which is beneficial to the subsequent separation process. After the full reflux is completed, the reflux ratio is adjusted to 4:3.5, and the liquid phase temperature is controlled to 72°C and the gas phase temperature is 62°C. The n-hexane fraction is extracted to obtain high-transmittance n-hexane, which is packaged and stored.
[0039] Example 2 This embodiment provides a method for improving the light transmittance of n-hexane, specifically: 1. Oxidation treatment Add industrial-grade n-hexane into the oxidation reactor, and then connect the reaction bottle and the ozone generator to ensure that the device system is well sealed; then place the oxidation reactor in an ice-water bath, and control the temperature of the oxidation reactor within the range of 0-5°C to avoid overheating and unnecessary side reactions; then turn on the ozone generator, control the ozone flow rate to 0.4L / min, and the ozone pressure to 0.2MPa, introduce ozone into the oxidation reactor, control the temperature and stir the reaction for 2h, and then complete the oxidation treatment; then, under stirring conditions, introduce inert gas (nitrogen) into the oxidation reactor to completely replace the ozone in the oxidation reactor to obtain an oxidized liquid (i.e., n-hexane after oxidation treatment).
[0040] Among them, industrial-grade n-hexane is prepared by cracking and fractionating crude oil; this embodiment uses conventional commercially available industrial-grade n-hexane prepared by the crude oil cracking method.
[0041] 2. Adsorption removal The modified molecular sieve is used to completely fill the adsorption column, and attention is paid to avoid filling dead corners and pores during the filling process; after the filling is completed, the adsorption column is connected to the flow meter and the collector to ensure that the device system is well sealed; the flow meter is turned on, the flushing flow rate of the oxidizing liquid is controlled to be 10mL / min, and the modified molecular sieve in the adsorption column is flushed with the oxidizing liquid for 3 times; after the flushing is completed, the flow rate of the oxidizing liquid is adjusted to 4mL / min, and the oxidizing liquid continues to flow through the adsorption column for continuous adsorption and removal to obtain the adsorption and removal liquid.
[0042] The amount of oxidation liquid used for each flushing is 550 mL.
[0043] The preparation method of the modified molecular sieve is as follows: 1) Preprocessing The 3A molecular sieve was placed in a calcining furnace, heated to 400°C in an inert gas (nitrogen) environment, kept warm for 40 minutes to remove impurities, and naturally cooled to room temperature to obtain a heat-treated product; the heat-treated product was then put into an ethanol solution with a volume concentration of 88%, stirred for 20 minutes, stirred and heated to 40°C, and the silane coupling agent KH-792 and bis(dioctyl pyrophosphate acyloxy)ethylene titanate were dripped into the solution while being kept warm and stirred, and the dripping time of the silane coupling agent KH-792 and bis(dioctyl pyrophosphate acyloxy)ethylene titanate was controlled to be 50 minutes; after the dripping was completed, the solution was kept warm and stirred for 7 hours, and the solid was separated by centrifugation at 11000 rpm. The solid was washed with deionized water, placed in a vacuum drying oven, and dried at 80°C for 12 hours in a vacuum environment of 0.07 MPa to obtain a pretreated product.
[0044] Among them, the weight ratio of 3A molecular sieve, ethanol solution, silane coupling agent KH-792, and bis(dioctyl pyrophosphate)ethylene titanate is 9:605:1:0.3.
[0045] 2) Composite modification The pretreated material was put into 8 times the weight of deionized water, stirred for 10 minutes, and then tetrapropylammonium hydroxide was added and stirred for 20 minutes; isopropyl aluminum and ethyl orthosilicate were added, stirred and heated to 30°C, kept stirring for 60 minutes, and then continued to stir and heat to 85°C, kept stirring for 22 hours to obtain a precursor solution; then the precursor solution was transferred into a high-pressure reactor, heated to 170°C, kept warm for crystallization for 55 hours, and then the solid was separated by centrifugation at 9500rpm. After the solid was washed with anhydrous ethanol and deionized water in turn, it was placed in a vacuum drying oven and dried at 100°C for 12 hours in a vacuum environment of 0.08MPa; then it was transferred into a calcining furnace, heated to 550°C at a heating rate of 3°C / min, kept warm for 4 hours, and naturally cooled to room temperature to obtain a calcined material.
[0046] The weight ratio of the pretreated material, tetrapropylammonium hydroxide, isopropyl aluminum and tetraethyl orthosilicate is 10:2:0.12:3.9.
[0047] 3) Post-processing The calcined product was immersed in 4 times the weight of ammonium nitrate solution, stirred and heated to 75°C, kept warm for 8 hours, and then centrifuged at 9500rpm to separate the solid. After the solid was washed with deionized water, it was placed in a vacuum drying oven and dried at 100°C for 12 hours in a vacuum environment of 0.08MPa; then it was transferred to a calcining furnace, heated to 400°C at a heating rate of 1.2°C / min, kept warm and calcined for 2 hours, and naturally cooled to room temperature to obtain a modified molecular sieve.
[0048] Wherein, the molar concentration of the ammonium nitrate solution is 0.2 mol / L.
[0049] 3. Distillation and impurity removal The adsorbed removal liquid is introduced into the distillation kettle, and the stirring heating and light component condensation systems of the distillation kettle are turned on. The heating temperature of the distillation kettle is set to 130°C, and the light component condensation temperature is set to 8°C. Under stirring conditions, the temperature of the distillation kettle is controlled to rise to 130°C and the distillation is kept warm. During the first hour of the distillation, full reflux is performed to promote the equilibrium between the liquid and gas phases in the distillation kettle, which is beneficial to the subsequent separation process. After the full reflux is completed, the reflux ratio is adjusted to 4:3, and the liquid phase temperature is controlled to 65°C and the gas phase temperature to 55°C. The n-hexane fraction is extracted to obtain high-transmittance n-hexane, which is packaged and stored.
[0050] Example 3 This embodiment provides a method for improving the light transmittance of n-hexane, specifically: 1. Oxidation treatment Add industrial-grade n-hexane into the oxidation reactor, then connect the reaction bottle and the ozone generator to ensure that the device system is well sealed; then place the oxidation reactor in an ice-water bath, and control the temperature of the oxidation reactor within the range of 0-5°C to avoid overheating and unnecessary side reactions; then turn on the ozone generator, control the ozone flow rate to 0.8L / min, the ozone pressure to 0.5MPa, introduce ozone into the oxidation reactor, control the temperature and stir the reaction for 3h, and then complete the oxidation treatment; then, under stirring conditions, introduce inert gas (nitrogen) into the oxidation reactor to completely replace the ozone in the oxidation reactor to obtain an oxidized liquid (i.e., n-hexane after oxidation treatment).
[0051] Among them, industrial-grade n-hexane is prepared by cracking and fractionating crude oil; this embodiment uses conventional commercially available industrial-grade n-hexane prepared by the crude oil cracking method.
[0052] 2. Adsorption removal The modified molecular sieve is used to completely fill the adsorption column, and attention is paid to avoid filling dead corners and pores during the filling process; after the filling is completed, the adsorption column is connected to the flow meter and the collector to ensure that the device system is well sealed; the flow meter is turned on, the flushing flow rate of the oxidizing liquid is controlled to be 15mL / min, and the modified molecular sieve in the adsorption column is flushed with the oxidizing liquid for 5 times; after the flushing is completed, the oxidizing liquid flow rate is adjusted to 5mL / min, and the oxidizing liquid continues to flow through the adsorption column for continuous adsorption and removal to obtain an adsorption and removal liquid.
[0053] The amount of oxidation liquid used for each flushing is 600 mL.
[0054] The preparation method of the modified molecular sieve is as follows: 1) Preprocessing The 3A molecular sieve was placed in a calcining furnace, heated to 500°C in an inert gas (nitrogen) environment, kept warm for 60 minutes to remove impurities, and naturally cooled to room temperature to obtain a heat-treated product; the heat-treated product was then put into an ethanol solution with a volume concentration of 92%, stirred for 30 minutes, stirred and heated to 45°C, and the silane coupling agent KH-792 and bis(dioctyl pyrophosphate acyloxy)ethylene titanate were dripped into the solution while being kept warm and stirred, and the dripping time of the silane coupling agent KH-792 and bis(dioctyl pyrophosphate acyloxy)ethylene titanate was controlled to be 60 minutes; after the dripping was completed, the solution was kept warm and stirred for 8 hours, and the solid was separated by centrifugation at 12000 rpm. The solid was washed with deionized water, placed in a vacuum drying oven, and dried at 85°C for 14 hours in a vacuum environment of 0.08 MPa to obtain a pretreated product.
[0055] Among them, the weight ratio of 3A molecular sieve, ethanol solution, silane coupling agent KH-792, and bis(dioctyl pyrophosphate)ethylene titanate is 10:65:1.2:0.4.
[0056] 2) Composite modification The pretreated material was put into 9 times the weight of deionized water, stirred for 20 minutes, and then tetrapropylammonium hydroxide was added and stirred for 30 minutes; isopropyl aluminum and ethyl orthosilicate were added, stirred and heated to 35°C, kept stirring for 90 minutes, and then continued to stir and heat to 90°C, kept stirring for 24 hours to obtain a precursor solution; then the precursor solution was transferred into a high-pressure reactor, heated to 180°C, kept warm for crystallization for 60 hours, and then the solid was separated by centrifugation at 10000rpm, and the solid was washed with anhydrous ethanol and deionized water in turn, and then placed in a vacuum drying oven, and dried at 105°C for 14 hours in a vacuum environment of 0.09MPa; then transferred to a calcining furnace, heated to 600°C at a heating rate of 4°C / min, kept warm for calcination for 5 hours, and naturally cooled to room temperature to obtain a calcined material.
[0057] The weight ratio of the pretreated material, tetrapropylammonium hydroxide, isopropyl aluminum and tetraethyl orthosilicate is 10.5:2.3:0.15:4.1.
[0058] 3) Post-processing The calcined product was immersed in an ammonium nitrate solution of 5 times its weight, stirred and heated to 80°C, and kept warm for 9 hours. The solid was separated by centrifugation at 10000rpm, washed with deionized water, placed in a vacuum drying oven, and dried at 105°C for 14 hours in a vacuum environment of 0.09MPa; then transferred to a calcining furnace, heated to 420°C at a heating rate of 1.6°C / min, kept warm and calcined for 3 hours, and naturally cooled to room temperature to obtain a modified molecular sieve.
[0059] Wherein, the molar concentration of the ammonium nitrate solution is 0.22 mol / L.
[0060] 3. Distillation and impurity removal The adsorbed removal liquid is introduced into the distillation kettle, and the stirring heating and light component condensation systems of the distillation kettle are turned on. The heating temperature of the distillation kettle is set to 150°C, and the light component condensation temperature is set to 10°C. Under stirring conditions, the temperature of the distillation kettle is controlled to rise to 150°C, and the distillation is kept warm. During the first 2 hours of the distillation, full reflux is performed to promote the equilibrium between the liquid and gas phases in the distillation kettle, which is beneficial to the subsequent separation process. After the full reflux is completed, the reflux ratio is adjusted to 4:6, and the liquid phase temperature is controlled to 75°C and the gas phase temperature is 65°C. The n-hexane fraction is extracted to obtain high-transmittance n-hexane, which is packaged and stored.
[0061] Comparative Example 1 The technical solution of Example 1 is adopted, but the difference is that in the preparation of the modified molecular sieve used for adsorption removal, the pretreatment step is omitted.
[0062] Comparative Example 2 The technical solution of Example 1 is adopted, which differs in that: in the preparation of the modified molecular sieve used for adsorption removal, the composite modification step and the post-treatment step are omitted; instead, the pretreated product is directly mixed with the commercially available ZSM-5 molecular sieve and then used as the modified molecular sieve in the adsorption removal step.
[0063] The weight ratio of the pretreated material to the ZSM-5 molecular sieve is 3:1.
[0064] The methods for improving the light transmittance of n-hexane in Examples 1-3 and Comparative Examples 1-2 were used to measure the purity (gas chromatography GC), water content, acidity (in terms of H + The results are shown in the following table:
[0065] The method for improving the transmittance of n-hexane in Example 1 was used. The modified molecular sieves in Example 1 and Comparative Examples 1-2 were used for continuous adsorption and removal for 240 hours. The purity (gas chromatography GC), moisture content, acidity (in terms of H + The results are shown in the following table:
[0066] It can be seen that the method for improving the light transmittance of n-hexane of the present invention adopts a three-stage purification process of oxidation-adsorption-distillation. In the oxidation treatment step, ozone is used as an oxidant to oxidize the industrial-grade n-hexane raw material, effectively removing aromatic hydrocarbon impurities (such as benzene, toluene, xylene, etc.) and double bond impurities (such as alcohol, ether, ketone, etc.) that affect ultraviolet absorption. The reaction conditions are mild and easy to control. The oxidation treatment effect is good and no new impurities are introduced to obtain an oxidized liquid; then the oxidized liquid continuously flows through an adsorption column filled with a modified molecular sieve for adsorption removal, and the impurities in the n-hexane are effectively removed. The invention can selectively adsorb the isomeric impurities of n-hexane (especially the isomeric impurities of n-hexane), effectively overcoming the problem that the isomeric impurities in n-hexane are difficult to separate due to their close boiling points. Meanwhile, in the preparation of the modified molecular sieve, the 3A molecular sieve is pre-modified by using a bisaminosilane coupling agent and a chelating titanate coupling agent, so as to promote the combination performance of the 3A molecular sieve with the in-situ generated ZSM molecular sieve in the subsequent composite modification step, and improve the long-term adsorption stability and adsorption effect of the modified molecular sieve finally prepared in the continuous adsorption removal. The pretreated product is used in the preparation process of ZSM molecular sieves, and the 3A molecular sieve is further compounded with the original ZSM molecular sieve by in-situ compounding, so as to achieve the coordination of large and small pores of the modified molecular sieve, improve its selective adsorption performance of impurities in the oxidizing solution, and synergistically improve the long-term adsorption stability and adsorption effect of the modified molecular sieve in continuous adsorption and removal; then in the post-treatment step, ammonium nitrate is used to perform ion exchange on the roasted product, and the pore structure of the modified molecular sieve is further optimized, so as to further improve the selectivity of the modified molecular sieve for impurities in continuous adsorption and removal. Adsorption performance and long-term adsorption stability; finally, the adsorption removal liquid is distilled and impurity-removed to obtain high-transmittance n-hexane; the aforementioned technical means cooperate and work synergistically with each other to effectively simplify the treatment process, and through the three steps of oxidation-adsorption-distillation, it can effectively treat the impurities (such as aromatic hydrocarbon impurities, oxygen-containing compound impurities, etc.) generated in the preparation process of n-hexane, and the adsorption effect on impurities in n-hexane is significant, effectively improving the transmittance of n-hexane, thereby avoiding the problems of low-transmittance n-hexane affecting detection sensitivity, reducing signal intensity, and causing background noise in liquid chromatography applications.
[0067] It can be seen from Comparative Example 1 that after the pretreatment step is omitted in the preparation of the modified molecular sieve, the 3A molecular sieve has not undergone surface pre-modification treatment with a bisaminosilane coupling agent and a chelating titanate coupling agent, and in the subsequent composite modification step, the binding performance of the 3A molecular sieve and the in-situ generated ZSM molecular sieve is reduced, and the long-term adsorption stability and adsorption effect of the modified molecular sieve finally prepared in continuous adsorption and removal are reduced.
[0068] It can be seen from Comparative Example 2 that the composite modification step and the post-treatment step are omitted in the preparation of the modified molecular sieve, and the pretreated material and the commercially available ZSM-5 molecular sieve are directly used to adsorb and remove the oxidizing liquid. The matching performance of the pretreated material and the ZSM-5 molecular sieve is reduced, the selective adsorption performance of impurities in the oxidizing liquid is reduced, and it is impossible to maintain the ideal long-term adsorption stability and adsorption effect in continuous adsorption and removal.
[0069] Unless otherwise specified, all percentages used in the present invention are by mass.
[0070] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving the light transmittance of n-hexane, characterized in that: The process includes the following steps: oxidation treatment, adsorption removal, and distillation to remove impurities; The oxidation treatment method is to use ozone to oxidize industrial-grade n-hexane to obtain an oxidation liquid; The adsorption removal method is that the oxidizing liquid continuously flows through an adsorption column filled with a modified molecular sieve to perform continuous adsorption removal to obtain an adsorption removal liquid; The distillation and impurity removal method comprises distilling the adsorption removal liquid to obtain high-transmittance n-hexane.
2. The method for improving the light transmittance of n-hexane according to claim 1, characterized in that: The oxidation treatment method is to introduce industrial-grade n-hexane into an oxidation reactor, control the temperature of the oxidation reactor to maintain within the range of 0-5°C; then continuously introduce ozone into the oxidation reactor, control the temperature and stir the reaction, and then use inert gas to completely replace the ozone in the oxidation reactor to obtain an oxidizing liquid.
3. The method for improving the light transmittance of n-hexane according to claim 2, characterized in that: During the oxidation treatment, the ozone flow rate is controlled to be 0.1-1 L / min and the ozone pressure is controlled to be 0.2-0.5 MPa; The temperature-controlled stirring reaction time is 2-3h.
4. The method for improving the light transmittance of n-hexane according to claim 1, characterized in that: The adsorption removal method is to control the oxidation liquid to flow continuously through an adsorption column filled with modified molecular sieves at a flow rate of 4-5 mL / min to perform continuous adsorption removal to obtain an adsorption removal liquid.
5. The method for improving the light transmittance of n-hexane according to claim 1, characterized in that: The modified molecular sieve is prepared by the following steps: pretreatment, composite modification, and post-treatment; The pretreatment method is as follows: 3A molecular sieve is calcined at 400-500° C. and then cooled, and then put into an ethanol solution, and at a temperature of 40-45° C., silane coupling agent KH-792 and bis(dioctyl pyrophosphate)ethylene titanate are added dropwise while stirring; after the addition is completed, the mixture is kept warm and stirred for 7-8 hours, and then the solid is separated and dried to obtain a pretreated product.
6. The method for improving the light transmittance of n-hexane according to claim 5, characterized in that: In the pretreatment, the dropping time of the silane coupling agent KH-792 and bis(dioctyl pyrophosphate acyloxy)ethylene titanate is controlled to be 50-60 min; The weight ratio of 3A molecular sieve, ethanol solution, silane coupling agent KH-792, and bis(dioctyl pyrophosphate acyloxy)ethylene titanate is 9-10:60-65:1-1.2:0.3-0.4; The volume concentration of the ethanol solution is 88-92%.
7. The method for improving the light transmittance of n-hexane according to claim 5, characterized in that: The composite modification method comprises the following steps: adding the pretreated material into deionized water, and after uniform dispersion, adding tetrapropylammonium hydroxide, and after uniform dispersion; adding isopropyl aluminum and ethyl orthosilicate, stirring and heating to 30-35° C., keeping the temperature and stirring, and then stirring and heating to 85-90° C., keeping the temperature and stirring to obtain a precursor solution; then transferring the precursor solution into a high-pressure reactor, heating to 170-180° C., keeping the temperature and crystallizing, separating out solids, washing the solids, and drying them; and then calcining at 550-600° C. to obtain a calcined product.
8. The method for improving the light transmittance of n-hexane according to claim 7, characterized in that: In the composite modification, the heat preservation and stirring time at a temperature of 30-35°C is 60-90 minutes; The heat preservation and stirring time at 85-90℃ is 22-24h; The crystallization time at 170-180℃ is 55-60h; The heating rate for calcination at 550-600°C is 3-4°C / min; The weight ratio of the pretreated material, tetrapropylammonium hydroxide, isopropyl aluminum and tetraethyl orthosilicate is 10-10.5:2-2.3:0.12-0.15:3.9-4.
1.
9. The method for improving the light transmittance of n-hexane according to claim 5, characterized in that: The post-treatment method is to immerse the roasted product in an ammonium nitrate solution, stir and heat it to 75-80°C, keep it warm for 8-9 hours, separate the solid, wash the solid, and dry it; then roast it at 400-420°C to obtain the modified molecular sieve; The molar concentration of the ammonium nitrate solution is 0.2-0.22 mol / L.
10. The method for improving the light transmittance of n-hexane according to claim 1, characterized in that: The method for rectifying and removing impurities is to introduce the adsorbed removal liquid into a distillation kettle, control the rectification temperature to be 130-150° C., the light component condensation temperature to be 8-10° C., and perform heat preservation rectification; The total reflux is carried out in the first 1-2 hours of the heat preservation distillation; after the total reflux is completed, the reflux ratio is adjusted to 4:1-6, and the liquid phase temperature is controlled to 65-75°C, the gas phase temperature is controlled to 55-65°C, and the n-hexane fraction is extracted to obtain high-transmittance n-hexane.
